Evaluation of pulsed-field gel electrophoresis as a typing system for Candida rugosa: comparison of karyotype and restriction fragment length polymorphisms. - Dib, J C (1996)
Nosocomial infections with Candida species have emerged as an increasingly important cause of morbidity and mortality in intensive care units. Ten Candida rugosa isolates from a previously documented cluster of C. rugosa infections in one hospital (nine burn unit isolates and one isolate from another hospital ward) and eight C. rugosa isolates recovered in a referral fungus testing laboratory (comparison isolates) from distinct geographic areas were investigated by molecular techniques. Isolates were from multiple anatomic sites. Pulsed-field gel electrophoresis (PFGE) of whole-cell DNA was performed with the 18 C. rugosa isolates as a marker of strain identity. The PFGE karyotypes of the C. rugosa isolates were demonstrated from four to seven chromosome bands. Karyotyping revealed the same PFGE pattern for the nine outbreak isolates from the burn unit, confirming clonal strain transmission. The isolate from the other hospital ward had a distinct karyotype. Distinct PFGE karyotype patterns were demonstrated for the eight comparison isolates. Restriction fragment length polymorphisms (RFLP) generated from whole-cell DNA digested with SfiI demonstrated the same RFLP pattern among outbreak isolates. Among comparison isolates, karyotyping distinguished some isolates that were indistinguishable by RFLP patterns. Karyotyping by PFGE appears to be the most useful molecular typing tool for discrimination among strains of C. rugosa and will be a useful marker for evaluating the epidemiology of future C. rugosa infections.